2021
DOI: 10.1155/2021/7019130
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Antimicrobial and Wound Healing Effects of Gold Nanoparticles Containing Abelmoschus esculentus (L.) Aqueous Extract

Abstract: Background. Wound healing is a complex process of replacing devitalized cellular structures and tissues with healthy cells and tissue. Nanotechnology has been increasingly proposed as a novel platform to treat wounds and skin regeneration. The aim of this study was to evaluate the antibacterial, antioxidant, cytotoxic, and cutaneous wound healing activities of phytosynthesized Au NPs using Abelmoschus esculentus (okra) and synthesized Au NPs by using the citrate synthesis method. The Ok Au NPs were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Our findings are also in concordance with other reports that showed that gold nanoparticles capping with natural products, such as quercetin derived from Abelmoschus esculentus (L.) (okra), or with epigallocatechin gallate and α-lipoic acid on linear wound enhanced wound healing [6,27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are also in concordance with other reports that showed that gold nanoparticles capping with natural products, such as quercetin derived from Abelmoschus esculentus (L.) (okra), or with epigallocatechin gallate and α-lipoic acid on linear wound enhanced wound healing [6,27,28].…”
Section: Discussionsupporting
confidence: 93%
“…The microscopic observation of regenerated tissues, colored by H&E and Mason Trichoma stains, revealed noticeable tissue regeneration enhanced by the topical application of CCS, which was by the previous outcomes of wound‐curing effects of CCS extracts 24 . Similarly, researchers have shown the wound‐healing potentials of CCS obtained from a variety of medicinal plants 42–44 …”
mentioning
confidence: 74%
“…24 Similarly, researchers have shown the wound-healing potentials of CCS obtained from a variety of medicinal plants. [42][43][44] The TGF-β1 is a well-known multifunctional polypeptide factor considered an important mediator of tissue regeneration (angiogenesis) and faster wound repair because of its modulatory action on…”
Section: Ccs Effects On Hydroxyprolyinementioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%